Epidemiological Study of Functional Dry Eye Disease in Working-class Population in Shanghai, China - Wang, Nianhong; Liu, Yan; Weng, Huan; Wang, Huiying; Xiao, Weibao (La Medicina del Lavoro, 2025)
Background: To investigate the current status, morbidity, and risk factors of functional dry eye disease (DED) in Shanghai’s working-class population and explore measures to fundamentally cure and prevent functional DED. Methods: A questionnaire form was used to record the data of the diagnosed functional DED working-class subjects in Shanghai, the results were recorded and analyzed. Additionally, the subjective symptoms of DED subjects and the respective clinical results were also recorded. The classification and corneal staining between subjects who wear contact lens or without were compared. The correlation of classification and corneal staining with their risk factors were also analyzed. Results: The risk factors of functional DED showed much in common though their works have professional particularity. Evaporative dry eye (EDE) accounts for a large proportion of DED (45.35%), many subjects co-exist symptoms and signs of mixed DED (32.64%). The age of 21-40 is the peak year range (70.4%). Contact lens, visual terminals, air-conditioner, decoration, stay up later, sleep disorder, smoking were risk factors in most functional DED subjects. Notably, contact lens is a leading risk factor to cause functional DED and ocular surface complications (both were p<0.01), while deep sleep seems to be a protective factor (p<0.01%). Conclusion: The incidence of functional DED in Shanghai is kept in a high level. Most risk factors are closely related to daily work and life, while they are almost reversible. Exploring and eradicating these daily risk factors seems to be a more preferable way to fundamentally control and prevent functional DED.